THE CORRELATION OF HEMOGLOBIN LEVELS AND EXTENT OF LESION IN THORAX RADIOGRAPHY EXAMINATION OF PULMONARY TUBERCULOSIS PATIENTS - Muhammad Zacky Hafiyyan Maulana; Dini Rachma Erawati; Yuyun Yueniwati (Department of Radiology, Medical Faculty, University of Brawijaya, 2025)
Hemoglobin is an important protein in erythrocytes that is useful for transporting oxygen throughout the body. Changes in hemoglobin levels are often associated with medical disorders, which are diagnostic indicators for several diseases, including pulmonary tuberculosis. Tuberculosis diagnosis is often carried out through a thorax radiography examination by looking at the extent of the lesion (minimal, moderate advanced, or far advanced). Low hemoglobin levels (anemia) are associated with biomarkers of tuberculosis severity. The objective of this research is to ascertain the correlation between hemoglobin levels and the extent of lesions in thorax radiography examination of patients with pulmonary tuberculosis. In this observational research, secondary data from patient medical records is analyzed. The subjects of this research were pulmonary tuberculosis patients at Dr. Saiful Anwar General Hospital, East Java, Indonesia. Using the Chi-square test, the data from 55 subjects were analyzed, and the findings showed a p-value < 0.001. With a p-value < 0.05, this research shows that hemoglobin levels are significantly correlated with the extent of lesions from thorax radiography examinations of pulmonary tuberculosis patients.